Fatty Acid Profile of Blood Plasma at Mating and Early Gestation in Rabbit - Imane Hadjadj; Anna-Katharina Hankele; Eva Armero; María-José Argente; María de la Luz García (Animals, 2021)
The aim of this study was to analyse the fatty acid (FA) profile of blood plasma at mating and 72 hpm by gas chromatography. Moreover, the correlation between FA and ovulation rate, normal embryos and compacted morulae was estimated. Palmitic, linoleic, oleic and stearic were the highest FA concentrations at mating and 72 hpm. Most long chain saturated and PUFA were higher at 72 hpm than at mating, while MUFA were higher at mating. SFA, MUFA and PUFA were high and positively correlated. Correlation was 0.643 between MUFA at mating and ovulation rate, and 0.781 between MUFA and normal embryos, respectively. Compacted morulae were slightly correlated with SFA at mating (0.465). In conclusion, the FA profile of plasma varies depending on the reproductive cycle of the rabbit female, adapting to energetic requirements at mating and early gestation. Moreover, positive correlations are found between fatty acids and ovulation rate and embryo development and quality.